Public investment and the Sustainable Development Goals - Muñoz La Riva, Waldir Adhemir (2022)
The scientific article developed addresses the analysis of the relationship between Public Investment in the Non-Criminal Justice System Modernization Program (PMSAJ) and compliance with the Sustainable Development Goals (SDGs) executed through the three investment projects attached to the program, which are: National Board of Justice (Investment Project “Improvement of the service delivery model of the National Board of Justice to achieve the proper implementation of the Electronic Judicial File”); Constitutional Court (Investment Project “Improvement of the service delivery model of the Constitutional Court to achieve the proper implementation of the Electronic Judicial File”) and Ministry of Justice and Human Rights (Investment Project “Improvement of free legal advice services to achieve the proper implementation of the Electronic Judicial File”). The research carried out showed that the components of each of the investment projects are associated with compliance with the SDGs. Said investigation was carried out relating the financial execution of the Program and the application of the questionnaires "CORE Questionnaire" and "Interview with Experts"; where it was possible to demonstrate the high correlation between both variables and the impact suggested by the execution of investment projects in favor of achieving the SDGs.